STUDY OF CONSUMER PREFERENCES TO SUPPORT THE MARKETING STRATEGY OF THE THRIFT CLOTHING BUSINESS - Faerrosa, Lady; Dethan, Stevany Hanalyna (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2023)
With the increasing number of thrift shops and traditional markets on Lombok Island, researchers view research in relation to consumer behavior and marketing strategies as very important. The purpose of this study is to analyze consumer preferences as a supporter of the marketing strategy of the thrift clothing business on Lombok Island. In-depth interviews were conducted with five key informants of this study who are business people and consumers of thrift clothing who have shopped at least five times at markets or thrift stores on Lombok Island. The results of this study show that thrift clothing consumers mostly make purchases offline of daily wear and clothing to work. In addition, consumers buy thrift clothes because of the availability of various brands from various countries such as Korea, Japan, and America. The reason for consumer preference in purchasing thrift clothing is because of the much cheaper price, much better quality of materials, the availability of various unique models to meet the needs of consumer fashion styles, and a little awareness of environmental sustainability. The result of this study provides an overview of consumer preference patterns that can be used in the preparation of marketing strategies, namely in terms of price, products, and distribution channels. Theoretically, the results of this study also enrich the wealth of knowledge in the field of consumer behavior, especially regarding consumer preferences in purchasing used clothes.